Kwietnica okazała Protaetia speciosissima (Scopoli, 1786) (Coleoptera: Scarabaeidae) w skrzynce lęgowej dla puszczyka Strix aluco L., 1758 w Dąbrowach Krotoszyńskich - Dolata, Paweł; Ekiert, Tomasz; Gryz, Jakub; Jaworski, Tomasz (Leśne Prace Badawcze, 2021)
This paper presents a new record of the rose chafer Protaetia speciosissima (Scopoli, 1786) (Coleoptera: Scarabaeidae), a rare beetle species associated with tree hollows. Specimens of this beetle were found in the oak forest in the Krotoszyn Forest District, west-central Poland, in nest-box for the tawny owl ( Strix aluco L., 1758) that had accumulated dead organic material. This finding suggests that it is possible for P. speciosissima to develop and reproduce outside its typical microhabitats.